Verify the following:
(a) 18 × [7 + (–3)] = [18 × 7] + [18 × (–3)]
(b) (–21) × [(– 4) + (– 6)] = [(–21) × (– 4)] + [(–21) × (– 6)]
Answers
Answered by
0
Answer:
18 × [7 + (–3)] = [18 × 7] + [18 × (–3)]
(b) (–21) × [(– 4) + (– 6)] = [(–21) × (– 4)] + [(–21) × (– 6)]
Answered by
8
Step-by-step explanation:
a) 18 x [7+(-3)] = [18 x 7 ] + [18 x (-3)]
18 x [7-3] = 126 + [-54]
18×4 = 126 -54
72 = 72
Hence verified
b) (–21) × [(– 4) + (– 6)] = [(–21) × (– 4)] + [(–21) × (– 6)]
-21 x [- 4 -6] = [-21 x -4] + [-21 x -6]
(-21) x (-10) = 84 + 126
210 = 210
Hence verified
hope it helps u.
plz mark as brilliant.
Similar questions